Проблеми впровадження інструментів електронної комерції в агробізнесі - Серських, Надія Сергіївна; Серских, Надежда Сергеевна; Serskykh, Nadiia (Мелітополь: ТДАТУ, 2014)
UK: В статті проаналізовано динаміку використання інформаційно-комунікаційних технологій в Україні,, розглянуто основні напрями та проблеми впровадження моделі електронної комерції В2В в діяльність підприємств аграрного сектору. Визначено шляхи вирішення цих проблем. EN: The modern era of globalization market processes leading to the need for advanced technology in all sectors of agriculture, especially the implementation of production. One of the priorities of globalization is the development of e-business and e-commerce in particular. It should be noted that the large farms lack the resources and opportunities for doing business with the use of innovation, while small producers remain aloof from the process. Nationwide trend of increasing number of Internet users is stored and southern regions of Ukraine. And Zaporizhzhya region intensity increase audience ranked third after Odessa and Crimea. Problems with access to communications and computer networks, low computer literacy and an understanding of the rural population about the need for innovation and imperfect regulatory framework for e-business - a number of factors that hinder the development of e-commerce in agribusiness. For small agricultural producers a priority e-commerce sector is Business-to-Business (B2B). The system provides for B2B trade transactions between businesses, as opposed to sector e-commerce B2C (Business-to-Concumer), while the second participant in the process necessarily end user. Small agricultural producers sell products that require further processing, because the B2B sector, we believe is best for them. To solve the above named issues should: to coordinate the activities of state and local government management on the formation of a developed information infrastructure; to create a national information resources, especially in the agricultural sector; to improve the legal framework concerning e-commerce and e-business; to provide access to information networks and communication services to residents of all settlements of Ukraine.
Keywords: електронна комерція; сектор В2В; електронний торговельний майданчик; електронна біржа